Izecksohniella puri sp. n., a new Brazilian cricket species (Orthoptera: Grylloidea: Phalangopsidae) from Atlantic Forest remnants - Sperber, Carlos Frankl; Rocha, Aline; Lopes-Andrade, Cristiano; Mesa, Alejo (Zootaxa, 2003)
Izecksohniella puri sp. n., a new cricket species from Atlantic Forest remnants, Minas Gerais State, Brazil, is here described, based on 52 specimens. Diagnostic to this species is the following combination of characters: males with both forewings coriaceous, conspicuous metanotal glands below the forewings, apices of genital projections enlarged. The description includes male, female, and nymph characters. Photographs of habitus, genitalia details and male cariotype, as well as drawings of coloration patterns and genitalia arrangement are provided. Similarities to Cacruzia bahiana and Vanzoliniella sambophilla are discussed.